Modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

By reacting highly electronegative acids with MOF materials to generate MOF materials containing highly electronegative anion groups, the interfacial properties of lithium-rich manganese-based positive electrode materials are improved, the problems of polarization and poor transmission performance are solved, and the electrochemical properties of the materials are improved.

CN120600803AActive Publication Date: 2025-09-05GANZHOU NOVA TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511079730.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-04
Publication Date
2025-09-05
Estimated Expiration
2045-08-04

AI Technical Summary

Technical Problem

Lithium-rich manganese-based positive electrode materials are prone to polarization and poor ion-electron transport performance during the cycle process, which limits their commercial application.

Method used

By reacting highly electronegative acids with MOF materials to generate MOF materials containing highly electronegative anion groups, and then solid-phase mixing with lithium-rich manganese-based positive electrode materials, the material interface performance is improved.

Benefits of technology

The ion transmission rate of the positive electrode material is improved, the polarization phenomenon is reduced, and the rate performance and electrochemical performance of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120600803A_ABST
    Figure CN120600803A_ABST
Patent Text Reader

Abstract

The invention discloses a modified lithium-rich manganese-based positive electrode material as well as a preparation method and application thereof, and belongs to the technical field of positive electrode materials. The preparation method comprises the following steps: (1) adding acid with high electronegativity into a solvent to obtain an acid solution; adding the MOF material into an acid solution, carrying out heating reaction for a set time, and carrying out solid-liquid separation to obtain an MOF material containing a high-electronegativity anion group; wherein the acid with high electronegativity is one or more of trifluoromethanesulfonic acid, trinitrobenzene sulfonic acid and cyanoacetic acid; and (2) mixing the MOF material containing the high electronegativity anion group with a lithium-rich manganese-based positive electrode material solid phase to obtain the modified lithium-rich manganese-based positive electrode material. The MOF material is treated by high-electronegativity acid and then is compounded with the lithium-rich manganese-based positive electrode material, so that the ion transmission rate of a positive electrode material interface can be effectively improved, the polarization phenomenon of the positive electrode material is reduced, and the rate capability of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of positive electrode materials, and specifically relates to a modified lithium-rich manganese-based positive electrode material and a preparation method and application thereof. Background Art

[0002] The mainstream cathode materials currently on the market include lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium iron phosphate (LFP), and ternary cathode materials (including NCM and NCA). Among these cathode materials, lithium-rich manganese-based materials are considered the most promising cathode materials for next-generation lithium-ion batteries due to their ultra-high specific capacity, high voltage characteristics, and significant cost advantages. These materials are key to achieving technological breakthroughs in high energy density for power lithium batteries. They boast a specific capacity of up to 300 mAh / g, far exceeding the discharge specific capacity of currently commercialized cathode materials such as lithium iron phosphate and ternary materials, and nearly double the actual capacity of currently commercialized cathode materials. Compared to common lithium cobalt oxide and nickel-cobalt-manganese ternary cathode materials, lithium-rich manganese-based materials offer lower costs and improved safety. However, these materials suffer from rapid capacity decay and are prone to polarization during cycling. Furthermore, their inherently poor reaction kinetics result in poor ion and electron transport. These issues have hindered the widespread commercial application of these materials. Summary of the Invention

[0003] In view of this, the object of the present invention is to provide a modified lithium-rich manganese-based positive electrode material and a preparation method and application thereof.

[0004] In a first aspect, the present invention provides a method for preparing a modified lithium-rich manganese-based positive electrode material, comprising the following steps: (1) Adding a highly electronegative acid to a solvent to obtain an acidic solution; adding a MOF material to the acidic solution, heating the solution for a set reaction time, and then separating the solid and liquid to obtain a MOF material containing a highly electronegative anion group; wherein the highly electronegative acid is one or more of trifluoromethanesulfonic acid (CF3SO3H), trinitrobenzenesulfonic acid (C6H3N3O9S), and cyanoacetic acid (C3H3NO2); (2) The MOF material containing highly electronegative anionic groups is solid-phase mixed with the lithium-rich manganese-based positive electrode material to obtain a modified lithium-rich manganese-based positive electrode material.

[0005] Preferably, in step (1), the MOF material is one or more of Mn-MOF, Ni-MOF, and Co-MOF; the solvent is one or more of ethanol, N,N-dimethylformamide, water, acetonitrile, dimethyl sulfoxide, and diethyl ether, and more preferably one or more of ethanol, N,N-dimethylformamide, acetonitrile, dimethyl sulfoxide, and diethyl ether.

[0006] Preferably, in step (1), the mass volume ratio of the highly electronegative acid to the solvent is (2.5-5.5) g:(45-90) mL, and the mass volume ratio of the MOF material to the acidic solution is 1 g:(50-100) mL.

[0007] Preferably, in step (1), the heating temperature is 70-90° C., and the set time is 2-6 hours.

[0008] Preferably, in step (1), the method for preparing the MOF material comprises the following steps: After the metal salt solution and the organic ligand solution are mixed, a hydrothermal reaction is carried out. After the reaction is completed, the solid and liquid are separated to obtain the MOF material.

[0009] Further preferably, the metal salt is one or more of manganese salt, nickel salt, and cobalt salt, specifically one or more of sulfate, nitrate, and chloride of manganese, nickel, and cobalt; and the concentration of the metal salt solution is 1-3 mol / L.

[0010] More preferably, the organic ligand is one or more of trimesic acid, phthalic acid, and isophthalic acid; and the molar ratio of the metal salt to the organic ligand is 1:(5-10).

[0011] More preferably, the hydrothermal reaction temperature is 120-160° C., and the hydrothermal reaction time is 18-36 h.

[0012] Preferably, in step (2), the chemical formula of the lithium-rich manganese-based positive electrode material is Li 1+m Mn 1-m-n X n O2, wherein: X is one or more of Ni, Co, Fe, Al, Zn, 0.1≤m≤0.4, 0≤n<0.6.

[0013] Preferably, in step (2), the mass ratio of the MOF material containing highly electronegative anion groups to the lithium-rich manganese-based positive electrode material is 0.01-0.05:1.

[0014] Preferably, in step (2), solid phase mixing is performed by ball milling.

[0015] In a second aspect, the present invention provides a modified lithium-rich manganese-based positive electrode material prepared using the aforementioned preparation method.

[0016] In a third aspect, the present invention provides an application of the aforementioned modified lithium-rich manganese-based positive electrode material in a lithium battery.

[0017] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: (1) The MOF material in the present invention is treated with a highly electronegative acid and then composited with a lithium-rich manganese-based positive electrode material, which can effectively increase the ion transfer rate at the interface of the positive electrode material, reduce the polarization phenomenon of the positive electrode material, and improve the rate performance of the material.

[0018] (2) The preparation method of the modified lithium-rich manganese-based positive electrode material in the present invention is simple and easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The cycling performance diagram of the batteries assembled with the positive electrode materials prepared in Examples 1 to 6 and Comparative Example 1. DETAILED DESCRIPTION

[0020] To facilitate understanding of the present invention, the present invention will be described in more comprehensive and detailed form below in conjunction with the accompanying drawings and preferred embodiments. However, the protection scope of the present invention is not limited to the following specific embodiments. Unless otherwise defined, all technical terms used hereinafter have the same meanings as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0021] As mentioned above, in the first aspect, the present invention provides a method for preparing a modified lithium-rich manganese-based positive electrode material, comprising the following steps: (1) Adding a highly electronegative acid to a solvent to obtain an acidic solution; adding a MOF material to the acidic solution, heating the solution for a set reaction time, and then separating the solid and liquid to obtain a MOF material containing a highly electronegative anion group; wherein the highly electronegative acid is one or more of trifluoromethanesulfonic acid (CF3SO3H), trinitrobenzenesulfonic acid (C6H3N3O9S), and cyanoacetic acid (C3H3NO2); (2) The MOF material containing highly electronegative anionic groups is solid-phase mixed with the lithium-rich manganese-based positive electrode material to obtain a modified lithium-rich manganese-based positive electrode material.

[0022] In the present invention, the MOF material is subjected to a thermal reaction with a highly electronegative acid solution. During the reaction, the anionic groups of the highly electronegative acid may exist in the pores or surface of the MOF material through adsorption or complexation, thereby obtaining a MOF material containing highly electronegative anionic groups. Therefore, when the MOF material containing highly electronegative anionic groups is used to modify the lithium-rich manganese-based material, its comprehensive electrochemical performance can be effectively improved.

[0023] Preferably, in step (1), the MOF material is one or more of Mn-MOF, Ni-MOF, and Co-MOF; the solvent is one or more of ethanol, N,N-dimethylformamide, water, acetonitrile, dimethyl sulfoxide, and diethyl ether, and more preferably one or more of ethanol, N,N-dimethylformamide, acetonitrile, dimethyl sulfoxide, and diethyl ether.

[0024] The solvent in the present invention is preferably an organic solvent. As a medium, an organic solvent can reduce the degree of acid ionization, preventing highly electronegative acids from affecting the structure of the MOF material. Highly electronegative acids are organic acids, which have stronger coordination abilities and can maximize the formation of MOF materials with highly electronegative anionic groups.

[0025] Preferably, in step (1), the mass volume ratio of the highly electronegative acid to the solvent is (2.5~5.5) g:(45~90) mL, including but not limited to 2.5:45, 4.5:45, 5.5:45, 2.5:60, 4.5:60, 5.5:60, 2.5:90, 4.5:90, 5.5:90, etc.; the mass volume ratio of the MOF material to the acidic solution is 1 g:(50~100) mL, including but not limited to 1 g:50 mL, 1 g:60 mL, 1 g:70 mL, 1 g:80 mL, 1 g:90 mL, 1 g:100 mL, etc.

[0026] In the present invention, by controlling the ratio of the MOF material, the solvent and the highly electronegative acid, it is possible to ensure that the MOF material can load more highly electronegative anionic groups while avoiding destruction of the structure of the MOF material.

[0027] Preferably, in step (1), the heating temperature is 70-90°C, including but not limited to 70°C, 75°C, 80°C, 85°C, 90°C, etc.; the set time is 2-6h, including but not limited to 2h, 3h, 4h, 5h, 6h, etc.

[0028] Preferably, in step (1), the method for preparing the MOF material comprises the following steps: After the metal salt solution and the organic ligand solution are mixed, a hydrothermal reaction is carried out. After the reaction is completed, the solid and liquid are separated to obtain the MOF material.

[0029] Further preferably, the metal salt is one or more of manganese salt, nickel salt, and cobalt salt; specifically one or more of sulfate, nitrate, and chloride of manganese, nickel, and cobalt; the concentration of the metal salt solution is 1 to 3 mol / L, including but not limited to 1 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, etc.

[0030] The use of manganese, nickel, and manganese MOF materials in the present invention can better improve the comprehensive electrochemical properties of lithium-rich manganese-based materials.

[0031] Further preferably, the organic ligand is one or more of trimesic acid, phthalic acid, and isophthalic acid; the molar ratio of the metal salt to the organic ligand is 1:(5-10), including but not limited to 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.

[0032] Further preferably, the hydrothermal reaction temperature is 120~160℃, including but not limited to 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, 160℃, etc.; the hydrothermal reaction time is 18~36h, including but not limited to 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, etc.

[0033] Preferably, in step (2), the chemical formula of the lithium-rich manganese-based positive electrode material is Li 1+m Mn 1-m-n X n O2, wherein: X is one or more of Ni, Co, Fe, Al, Zn, 0.1≤m≤0.4, 0≤n<0.6.

[0034] Preferably, in step (2), the mass ratio of the MOF material with highly electronegative anion groups to the lithium-rich manganese-based positive electrode material is 0.01 to 0.05:1, including but not limited to 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, etc.

[0035] Preferably, in step (2), solid phase mixing is performed by ball milling.

[0036] In a second aspect, the present invention provides a modified lithium-rich manganese-based positive electrode material prepared using the aforementioned preparation method.

[0037] In a third aspect, the present invention provides an application of the aforementioned modified lithium-rich manganese-based positive electrode material in a lithium battery.

[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0039] Preparation Example 1 Lithium-rich manganese-based material Li 1.1 Mn 0.6 Co 0.3 Preparation of O2 0.067 mol MnSO4·H2O and 0.033 mol CoSO4·6H2O were dissolved in deionized water to prepare a 2 mol / L metal ion solution, which was then added to a continuous stirred tank reactor under nitrogen atmosphere. 4 mol / L NaOH precipitant and 20 wt% NH3·H2O complexing agent were continuously added to maintain the pH of the reaction solution within the range of 10-11. After fully reacting for 40 h, solid-liquid separation was performed, and the solid product was washed with water, washed with alcohol, and dried to obtain Mn. 0.67 Co 0.33 (OH)2. 0.1 molMn 0.67 Co 0.33 After (OH)2 was mechanically mixed with 0.123 mol of lithium hydroxide, it was placed in a muffle furnace and sintered at 980 ° C for 20 h to obtain Li 1.1 Mn 0.6 Co 0.3 O2.

[0040] Preparation Example 2 Lithium-rich manganese-based material Li 1.2 Mn 0.6 Fe 0.2 Preparation of O2 0.075 mol MnSO4·H2O and 0.025 mol FeSO4·6H2O were dissolved in deionized water to prepare a 2 mol / L metal ion solution, which was then added to a continuous stirred tank reactor under nitrogen atmosphere. 4 mol / L NaOH precipitant and 20 wt% NH3·H2O complexing agent were continuously added to maintain the pH of the solution within the range of 10-11. After sufficient reaction for 40 h, solid-liquid separation was performed, and the solid product was washed with water, washed with alcohol, and dried to obtain Mn. 0.75 Fe 0.25 (OH)2. 0.1 molMn 0.75 Fe 0.25 After (OH)2 was mechanically mixed with 0.154 mol of lithium hydroxide, it was placed in a muffle furnace and sintered at 1100 ° C for 10 h to obtain Li 1.2 Mn 0.6 Fe 0.2 O2.

[0041] Preparation Example 3 Preparation of Ni-MOF 0.1 mol of nickel sulfate was dissolved in 35 mL of deionized water to obtain a nickel sulfate solution; 0.8 mol of phthalic acid was dispersed in 300 mL of DMF to obtain an organic ligand solution; the nickel sulfate solution and the organic ligand solution were mixed and placed in a polytetrafluoroethylene hydrothermal reactor. After hydrothermal reaction at 140°C for 24 hours, the Ni-MOF material was obtained after filtration, washing and drying.

[0042] Preparation Example 4 Preparation of Mn-MOF 0.1 mol manganese nitrate was dissolved in 100 mL deionized water to obtain a manganese nitrate solution; 0.5 mol isophthalic acid was dispersed in 300 mL DMF to obtain an organic ligand solution; the manganese sulfate solution and the organic ligand solution were mixed and placed in a polytetrafluoroethylene hydrothermal reactor. After hydrothermal reaction at 120°C for 36 hours, the product was filtered, washed and dried to obtain the Mn-MOF material.

[0043] Preparation Example 5 Preparation of Co-MOF 0.1 mol of cobalt nitrate was dissolved in 50 mL of deionized water to obtain a cobalt nitrate solution; 1 mol of trimesic acid was dispersed in 500 mL of dimethylformamide (DMF) to obtain an organic ligand solution; the cobalt nitrate solution and the organic ligand solution were evenly mixed and placed in a polytetrafluoroethylene hydrothermal reactor. After hydrothermal reaction at 160°C for 18 hours, the product was filtered, washed, and dried to obtain the Co-MOF material.

[0044] Example 1 4.5g trifluoromethanesulfonic acid was dissolved in 60mL DMF to form organic solution A. 1g Ni-MOF material prepared in Preparation Example 3 was dispersed in the organic solution A. After heating at 80℃ for 4h, solid-liquid separation was performed to obtain MOF material containing highly electronegative anion groups. 0.15g MOF material containing highly electronegative anion groups and 5g Li prepared in Preparation Example 1 were mixed. 1.1 Mn 0.6 Co 0.3 The O2 material is ball-milled and solid-phase mixed to obtain a modified lithium-rich manganese-based positive electrode material.

[0045] Comparative Example 1 0.15g Ni-MOF material, 5g Li prepared in Preparation Example 1 1.1 Mn 0.6 Co 0.3 The O2 material is ball-milled and solid-phase mixed to obtain a modified lithium-rich manganese-based positive electrode material.

[0046] Example 2 The method is basically the same as Example 1, except that: DMF is replaced with an equal volume of deionized water, that is, 4.5 g of trifluoromethanesulfonic acid is dissolved in 60 mL of deionized water to form solution A.

[0047] Example 3 The same as Example 1, except that 0.05g of MOF material containing highly electronegative anion groups and 5g of Li prepared in Preparation Example 1 were used. 1.1 Mn 0.6 Co 0.3 O2 materials are ball-milled for solid phase mixing.

[0048] Example 4 The same as Example 1, except that 0.25g of MOF material containing highly electronegative anionic groups and 5g of Li prepared in Example 1 were used. 1.1 Mn 0.6 Co 0.3 O2 materials are ball-milled for solid phase mixing.

[0049] Example 5 Dissolve 1.0g of cyanoacetic acid and 1.5g of trifluoromethanesulfonic acid in 90mL of ethanol to form an organic solution A. Disperse 0.96g of the Co-MOF material prepared in Preparation Example 5 in the organic solution A. Heat the mixture at 90℃ for 2h and then separate the solid and liquid to obtain a MOF material containing highly electronegative anionic groups. Dissolve 0.15g of the MOF material containing highly electronegative anionic groups and 5g of the Li-ion battery prepared in Preparation Example 2 in the organic solution A. 1.2 Mn 0.6 Fe 0.2 The O2 material is ball-milled and solid-phase mixed to obtain a modified lithium-rich manganese-based positive electrode material.

[0050] Example 6 Dissolve 5.4g of trinitrobenzenesulfonic acid in 45mL of deionized water to form solution A, disperse 0.96g of the Mn-MOF material prepared in Preparation Example 4 in the above solution A, heat at 70℃ for 6h, and separate the solid and liquid to obtain the MOF material containing highly electronegative anion groups. 1.2 Mn 0.6 Fe 0.2 The O2 material is ball-milled and solid-phase mixed to obtain a modified lithium-rich manganese-based positive electrode material.

[0051] The positive electrode materials prepared in Examples 1-6 and Comparative Example 1 were assembled into batteries. The materials were weighed and ground to a mass ratio of 8:1:1 for positive electrode material: conductive graphite: PVDF. An appropriate amount of N-methylpyrrolidone (NMP) was then added dropwise and the grinding and stirring continued to form a uniform slurry. The slurry was evenly coated onto aluminum foil using a mold to a thickness of 200 μm. The slurry was dried in a drying oven at 90°C for 10 hours and then cut into 12 mm diameter discs. The batteries were assembled in a glove box using the discs as the positive electrodes and the lithium foil as the negative electrodes. The electrolyte (comprising a solvent and LiPF6, with a LiPF6 concentration of 1 mol / L and a 1:1:1 volume ratio of EC, DEC, and DMC) was used as the electrolyte. The performance test of the assembled battery was carried out. The assembled battery was placed in the LAND2001CT battery test box for charge and discharge test. The test was carried out at 25℃, 1C, and a cycle voltage of 2.8~4.7V. The number of cycles was 100. The test results can be seen in Figure 1 and Table 1.

[0052] Table 1 from Figure 1 As can be seen from the data in Table 1, the specific capacity and cycle performance of the battery assembled with the positive electrode material prepared in Example 1 are significantly improved compared to Comparative Example 1. This may be because the highly electronegative anionic groups can increase the ion transfer rate of the positive electrode material, reduce polarization, and thus improve the comprehensive electrochemical performance of the positive electrode material. Compared with Example 1, Example 2 uses water as a solvent for the highly electronegative acid. The specific capacity and cycle stability of the battery assembled with the corresponding positive electrode material are somewhat lower than those in Example 1. This may be because the highly electronegative acid has a large degree of ionization in the aqueous solution and is too acidic, which slightly destroys the framework of the MOF, resulting in a decrease in its specific capacity and cycle stability. The amount of MOF material containing highly electronegative anionic groups added in Examples 3 and 4 will have a certain fluctuation in the performance of the corresponding positive electrode material, indicating that the MOF material containing highly electronegative anionic groups has an optimal addition amount. The process parameters were adjusted in Examples 5 and 6, and the specific capacity and cycle stability of the battery assembled with the corresponding positive electrode material fluctuated to a certain extent, but the overall performance was good.

[0053] The above embodiments are intended only to illustrate the technical concepts and features of the present invention. Their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent changes or modifications made in accordance with the spirit of the present invention are intended to be covered by the scope of protection of the present invention.

Claims

1. A method for preparing a modified lithium-rich manganese-based positive electrode material, characterized in that: The following steps are involved: (1) adding a highly electronegative acid to a solvent to obtain an acidic solution; adding a MOF material to the acidic solution, heating the solution for a set reaction time, and then separating the solid and the liquid to obtain a MOF material containing a highly electronegative anion group; wherein the highly electronegative acid is one or more of trifluoromethanesulfonic acid, trinitrobenzenesulfonic acid, and cyanoacetic acid; (2) The MOF material containing highly electronegative anionic groups is solid-phase mixed with the lithium-rich manganese-based positive electrode material to obtain a modified lithium-rich manganese-based positive electrode material.

2. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In the step (1), the MOF material is one or more of Mn-MOF, Ni-MOF, and Co-MOF; The solvent is one or more of ethanol, N,N-dimethylformamide, water, acetonitrile, dimethyl sulfoxide, and diethyl ether; The mass volume ratio of highly electronegative acid to solvent is (2.5~5.5)g:(45~90)mL; The mass volume ratio of MOF material to acidic solution is 1g:(50~100)mL.

3. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The solvent is one or more of ethanol, N,N-dimethylformamide, acetonitrile, dimethyl sulfoxide, and diethyl ether.

4. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1 or 2, characterized in that: In the step (1), the heating temperature is 70-90°C and the set time is 2-6 hours.

5. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1 or 2, characterized in that: In step (1), the preparation method of MOF material includes the following steps: After the metal salt solution and the organic ligand solution are mixed, a hydrothermal reaction is carried out. After the reaction is completed, the solid and liquid are separated to obtain the MOF material.

6. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: The metal salt is one or more of manganese salt, nickel salt, and cobalt salt, specifically one or more of sulfate, nitrate, and chloride of manganese, nickel, and cobalt; the concentration of the metal salt solution is 1 to 3 mol / L; The organic ligand is one or more of trimesic acid, phthalic acid, and isophthalic acid; and the molar ratio of the metal salt to the organic ligand is 1:(5-10).

7. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In the step (2), the chemical formula of the lithium-rich manganese-based positive electrode material is Li 1+m Mn 1-m-n X n O2, wherein: X is one or more of Ni, Co, Fe, Al, Zn, 0.1≤m≤0.4, 0≤n<0.

6.

8. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In the step (2), the mass ratio of the MOF material containing highly electronegative anion groups to the lithium-rich manganese-based positive electrode material is 0.01-0.05:

1.

9. A modified lithium-rich manganese-based positive electrode material, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the modified lithium-rich manganese-based positive electrode material according to claim 9 in a lithium battery.

Citation Information

Patent Citations

  • Lithium-sulfur battery positive electrode material based on manganese-cluster-based MOF and preparation method and application thereof

    CN109360974A

  • Preparation method and application of MOF-74 derived carbon-coated cobalt-nickel bimetallic sulfide for negative electrode of sodium-ion battery

    CN112436145A

  • Preparation method of MOF-5 containing three carboxyl functional groups and application of MOF-5 in high-temperature potassium ion battery

    CN113948699A

  • MOF-coated ternary positive electrode material as well as preparation method and application thereof

    CN116230876A

  • Electrodes having electrode additive for high performance batteries and applications of same

    WO2020167725A1